Photoreductive chlorine elimination from a Ni(iii)Cl2 complex supported by a tetradentate pyridinophane ligand. Issue 59 (1st July 2021) - Na, Hanah; Watson, Michael B.; Tang, Fengzhi; Rath, Nigam P.; Mirica, Liviu M.
Abstract : We report a facile photoreductive chlorine elimination reaction from a stable Ni(iii ) dichloride complex supported by a tetradentate pyridinophane N-donor ligand. Abstract : Herein we report the isolation, characterization, and photoreactivity of a stable Ni III dichloride complex supported by a tetradentate pyridinophane N-donor ligand. Upon irradiation, this complex undergoes an efficient photoreductive chlorine elimination reaction, both in solution and the solid-state. Subsequently, the Ni III Cl2 species can be regenerated via a reaction with PhICl2 .